Perceived deterrents to classified staff's voluntary participation in staff development activities - Reed, Nancy L., author; Nelson, Barbara J., 1949-, advisor; Richburg, Robert W. (Robert Williams), committee member; Smith, Patricia, committee member; Darkenwald, Gordon G., committee member (Colorado State University. Libraries, 1994)
The purpose of this study was to identify the deterrents to public higher education classified staff's voluntary participation in staff development activities. The population was classified staff at the three Colorado State University System institutions: Colorado State University, Fort Lewis College, University of Southern Colorado. The sample population was asked to respond to the Deterrents to Participation Scale--Staff Development (DPS-SD), a modified form of the Deterrents to Participation Scale- -General Form (DPS-G). The survey asked thirty-five questions, comprising six participation deterrent factors, and nine demographic questions. A correlational design was utilized to study the relationships between the participation deterrents perceived by classified staff and their demographics and the relationships between classified staff's perceived participation deterrents and those perceived by the personnel/human resource services directors of the three campuses.
Department Head: Nancy K. Hartley.
Keywords: deterrents to participation scale-staff development; DPS-SD; deterrent factors; Universities and colleges -- Employees -- In-service training; State governments -- Officials and employees -- In-service training; Employer-supported education